Critical ventilation velocity of two fire sources with different separating distances in road tunnel. (July 2019) - Zhang, Shaogang; Shi, Long; Wang, Jinhui; Li, Xianbin; Han, Yuedong; He, Kun; Cheng, Xudong
Critical ventilation velocity is an important parameter for the design of road tunnel, while the situation of two fire sources should be considered due to the high probability of two crashed vehicles or fire propagation. The influences of separating distance between two fire sources on the critical ventilation velocity were investigated numerically after the experimental validation of numerical tool. The trend of the dimensionless critical velocity along the separating distance can be divided into three regions, including limited influence, fast decrease, and slight fluctuation. As the separating distance keeps increasing, the fire plumes transform from completely merged to completely separate. The different merging behaviors of fire plumes are the main reasons of showing various critical ventilation velocities with different separating distances. Finally, an empirical model was developed to predict the dimensionless critical ventilation velocity of double fire sources with different separating distances in the longitudinally ventilated road tunnel.